Measuring product sustainability using fuzzy method - Hemdi, A. R. (IEOM Society, 2016)
Sustainable conscious product is a product that has little or no impact on the environment during its life cycle. Hence, designing and developing a sustainable product with consideration of three main elements such as environment, social and economic aspects are needed. Within these elements, there are many sub-sustainability parameters need to be considered when sustainability analysis is carried out which include pollution, cost, energy, health, acidification and others. The inclusion of these parameters and the uncertainty data increases the complexity in decision making process with respect to sustainable development as it not only evaluates the current situation but also the prediction and strategic decision for the future. Therefore, a methods and tools are required in assisting the designers and decision makers to develop sustainable product. Hence, this paper presents a developed methodology of product sustainability analysis using fuzzy technique. The fuzzy logic approach is embedded into the evaluation process as it has a capability to handle severe uncertainty and ability to evaluate multi criteria data simultaneously. A case study of automotive components is presented to demonstrate the capability of fuzzy technique in sustainability evaluation.